2018
DOI: 10.2298/vsp160701239v
|View full text |Cite
|
Sign up to set email alerts
|

Rhinoplasty without nasal packing and splinting

Abstract: Background/Aim. Most surgeons, at the end of corrective rhinoplasty, use endonasal tamponade and external splinting, primarily because of hemostasis and immobilization. Possible complications of this surgery are various. Pain, nose edema, palpebral swelling and ecchymosis, are the most common and usual. The aim of our study was to evaluate the incidence of nonaesthetic complications and the efficiency of corrective rhinoplasty without the use of tamponade and external splint. Methods. One hundred and fiftyone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…12 The other three studies reviewed by Khan et al were retrospective case series of rhinoplasty patients who did not receive postoperative splints. [13][14][15] Across 2385 total patients, the collective results demonstrated that splinting was not necessary to achieve desirable aesthetic outcomes. Taken in consideration with the previous study described, the efficacy of compression therapy after rhinoplasty may depend on the method of application, with evidence favoring elastic bandaging over nasal splinting to reduce edema and ecchymosis postoperatively.…”
Section: Uses In Facial Surgerymentioning
confidence: 99%
“…12 The other three studies reviewed by Khan et al were retrospective case series of rhinoplasty patients who did not receive postoperative splints. [13][14][15] Across 2385 total patients, the collective results demonstrated that splinting was not necessary to achieve desirable aesthetic outcomes. Taken in consideration with the previous study described, the efficacy of compression therapy after rhinoplasty may depend on the method of application, with evidence favoring elastic bandaging over nasal splinting to reduce edema and ecchymosis postoperatively.…”
Section: Uses In Facial Surgerymentioning
confidence: 99%